Design consideration of phthalocyanines as sensitizers for enhanced sono-photodynamic combinatorial therapy of cancer - Lindokuhle Cindy Nene; Heidi Abrahamse (Elsevier, 2024)
Cancer remains one of the diseases with the highest incidence and mortality globally. Conventional treatment modalities have demonstrated threatening drawbacks including invasiveness, non-controllability, and development of resistance for some, including chemotherapy, radiation, and surgery. Sono-photodynamic combinatorial therapy (SPDT) has been developed as an alternative treatment modality which offers a non-invasive and controllable therapeutic approach. SPDT combines the mechanism of action of sonodynamic therapy (SDT), which uses ultrasound, and photodynamic therapy (PDT), which uses light, to activate a sensitizer and initiate cancer eradication. The use of phthalocyanines (Pcs) as sensitizers for SPDT is gaining interest owing to their ability to induce intracellular oxidative stress and initiate toxicity under SDT and PDT. This review discusses some of the structural prerequisites of Pcs which may influence their overall SPDT activities in cancer therapy.